The God of Small Things - Roy, Arundhati (New Delhi India Ink Publishing, 1997)
The story of an Indian family during the 1969 Communist disturbances in Kerala province. It is told through the eyes of a boy and his sister who are the children of a rich rubber planter. Politics, family drama, illicit love. A debut in fiction.